EFEKTIVITAS TEKNIK MODELING UNTUK MENINGKATKAN EMPATI MAHASISWA PRODI BK UNIVERSITAS AHMAD DAHLAN - Tri Sutanti (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
Student college of guidance and counseling program as a counselors candidate is required to have concern for others, including empathy. This study aims to determine effectiveness modeling techniques to increase empathy in students majoring in guidance and counseling University of Ahmad Dahlan in Yogyakarta. The method used in this research is pre experiment with one group pretest-posttest with sampling through purposive sampling technique. The samples are 10 students majoring in guidance and counseling Ahmad Dahlan University Yogyakarta. Data collected by using a scale of empathy that has been proven valid and reliable and by using observation sheet of communicative empathy. The results showed that modeling techniques can effectively increase empathy in students. The results of Wilcoxon statistical test showed that the value of Z = -2810 with p = 0.005 (<0.05), which means there is a significant difference level of empathy before treatment (pre-test) and after the treatment (post-test). The results could be used as consideration for educators in universities in order to develop empathy in students.